2007
DOI: 10.1080/01926230701748198
|View full text |Cite
|
Sign up to set email alerts
|

The Demonstration of Immunohistochemical Biomarkers in Methyl Methacrylate-Embedded Plucked Human Hair Follicles

Abstract: Plucked human hair follicles have been proposed as a potential surrogate for tumour tissue for measuring the effect of drugs on pharmacodynamic biomarkers in drug intervention studies. We describe a new technique of embedding plucked hair follicles in the acrylic resin, methyl methacrylate, and the immunohistochemical demonstration of six potential biomarkers (Ki67, EGFR, phospho-p27, phospho-histone H3, phospho-MAPK and phospho-Rb) in de-plasticised sections. The advantages of this technique over those that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Hair follicle cells are among the most rapidly proliferating cells in the body and are therefore sensitive to agents that damage DNA. Other studies have demonstrated that antibody-based protein detection methods are effective in hair follicle cells (46, 47). One obvious limitation of our model is that decreased concentrations of the drugs across the surface area of the skin may result in higher doses being required to observe an effect in hair follicles.…”
Section: Discussionmentioning
confidence: 99%
“…Hair follicle cells are among the most rapidly proliferating cells in the body and are therefore sensitive to agents that damage DNA. Other studies have demonstrated that antibody-based protein detection methods are effective in hair follicle cells (46, 47). One obvious limitation of our model is that decreased concentrations of the drugs across the surface area of the skin may result in higher doses being required to observe an effect in hair follicles.…”
Section: Discussionmentioning
confidence: 99%
“…The use of plucked hair follicles allows for the measurement of pharmacodynamic response(s) that is noninvasive and allows for repeated sampling without unduly stressing the subject, although care must be taken to ensure sample quality. Plucked hair follicles can be evaluated by immunohistochemistry or immunofluorescence to identify up-or downregulation of specific markers, such as Ki-67, EGFR, phospho-p27, phosphor-histone H3, phosphor-MAPK, or phosph-Rb (Randall and Foster 2007). Plucked follicles are also amenable to image analysis in order to quantify treatment-related changes of specific markers.…”
Section: Plucked Human Scalp Hair Follicle Analysismentioning
confidence: 99%
“…Immunohistochemistry U87MG tumor xenograft sections (5 mm thick) were dewaxed and rehydrated as described previously (Randall and Foster 2007). The following antigen retrieval techniques were then applied: no pretreatment, incubation for ten minutes with Proteinase K (Dako UK Ltd., Cambridgeshire, UK), or two minutes of microwave treatment at 110 C in either citrate (pH 6.0) or EDTA (pH 8.0) buffer.…”
Section: In Vitro Studiesmentioning
confidence: 99%